Economic cost and benefit of watershed conservation the case of Busol watershed - Ancheta, Milagros Ramona Valere D.; Bantasan, Dorothy D. (2013)
The Busol Watersheds serves as one of the major water sources in Baguio City and its neighboring municipality, La Trinidad. Aside from water, the watershed's forest cover also benefits surrounding communities by helping prevent soil erosion, and also by improving air and soil quality. Despite being a protected area, residential and agricultural activities continue to persist causing the forest cover to decrease. Watershed conservation programs and actions have been initiated by designated institutions in the city in order to preserve the watershed along with the benefits that it is able to give. Although, these conservation efforts may be able to generate certain social benefits, they also come at a cost. The study aims to determine whether or not the benefits generated by these conservation programs outweigh the cost of implementing them. One of the valuation which was used in order to quantify the value of the social benefits given by the watershed is the Philippine Economic Environmental Natural Resource Accounting(PEENRA) procedure, which measures the potential market value of tress in the watershed if they were to be sold as lumber. Another social value which was considered was the watershed's water yield. The value of the watershed in terms of improving air and soil quality and other non-use values such as cultural and aesthetic values were not included in the study because of the difficulty in quantifying such values in monetary terms. The value of the cost of conservation programs was limited to the annual maintenance cost allocated by the Baguio Water District and Department of Environmental and Natural Resources(CAR). Other opportunity costs such as the potential profit from commercial, residential or agricultural activities were not longer included in the study because of limitations in time, data and resources. Based on the attained values on social costs and benefits, the study was able to determine that there was a positive net social benefit from conservation programs in the Busol Watershed, wherein the benefits of these conservation efforts were greater than the cost in implementing them -- Author's abstract.